Resilient routing in ad hoc wireless sensor networks - Tehmina Karamat Khan; Taimur Karamat; Asad Ullah Shah; Umair Aitimad (Mehran University Research Journal of Engineering and Technology)
Ad hoc Wireless Sensor Networks (WSNs) are specialized networks comprising a collection of sensor nodes that communicate to perform a specific task or record data in a decentralized manner. A considerable amount of work has been done regarding security, power saving, and other issues related to ad hoc wireless sensor networks, but there have been fewer efforts to improve performance, optimal utilization, and minimize packet loss. This paper has devised an algorithm for identifying reliable routes for efficient and intelligent packet transmission in wireless network topology. A decision-based tree mechanism for routing has been developed, capable of establishing routes in an ad-hoc sensor network that can be transformed into a logical dual ring. The system also proposes embedding resilience and reliability features from the Resilient Packet Ring (RPR) and Quality of Service (QoS) mechanisms. The proposed scheme is also applicable to Fog/Edge Networks (FENs). It aims to create an easily deployable and adaptable routing protocol that leverages all devices to support seamless mobile-to-mobile communications and wireless interfaces. Besides, it performs effectively across a wide range of connectivity scenarios in uncertain FEN environments.